The effects and potential applications of concentrated growth factor in dentin–pulp complex regeneration - Zixia Li; Liu Liu; Liu Wang; Dongzhe Song (2021)
Abstract The dentin–pulp complex is essential for the long-term integrity and viability of teeth but it is susceptible to damage caused by external factors. Because traditional approaches for preserving the dentin–pulp complex have various limitations, there is a need for novel methods for dentin–pulp complex reconstruction. The development of stem cell-based tissue engineering has given rise to the possibility of combining dental stem cells with a tissue-reparative microenvironment to promote dentin–pulp complex regeneration. Concentrated growth factor, a platelet concentrate, is a promising scaffold for the treatment of dentin–pulp complex disorders. Given its characteristics of autogenesis, convenience, usability, and biodegradability, concentrated growth factor has gained popularity in medical and dental fields for repairing bone defects and promoting soft-tissue healing. Numerous in vitro studies have demonstrated that concentrated growth factor can promote the proliferation and migration of dental stem cells. Here, we review the current state of knowledge on the effects of concentrated growth factor on stem cells and its potential applications in dentin–pulp complex regeneration.